PENGARUH MODEL PEMBELAJARAN SEARCH, SOLVE, CREATE, AND SHARE (SSCS) TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS VIII SMPN 29 PADANG - Naziroah, Zelvia Ulfatul (Jurnal Edukasi dan Penelitian Matematika, 2024)
Learning outcomes are the main indicator in assessing the success of the learning process. If the learning outcomes obtained increase, then the learning process is considered successful. However, students in class VIII of SMP 29 Padang still have low learning outcomes. Applying the Search, Solve, Create, And Share (SSCS) model is one solution. The purpose of this study is to describe student learning achievement during the application of the SSCS Learning Model and to compare whether the mathematics learning outcomes of students who use this model are superior to students who learn through direct learning in class VIII of SMPN 29 Padang. This study uses a quasi-experimental method with an unequal posttest-only control group research design. In this study, the population was students in class VIII of SMPN 29 Padang, class VIII 5 and VIII 6 as samples. This study used a final learning outcome test tool in the form of an essay. Based on data analysis using the t-test, the  was obtained. Because ,  is rejected and  is accepted. Therefore, it can be concluded that the mathematics learning outcomes of students who apply the SSCS Learning Model are superior to those of students who apply direct learning in class VIII of SMPN 29 Padang.Keywords– Search, solve, create, and share models, learning outcomes, direct learning